Predictors of loss to follow-up among people living with HIV on antiretroviral therapy in a rural health facility using paper-based records - Abugah, Michael; Yabelang, Angela Mwinorme; Akorlie, John Kobla; Mahama, Haruna; Abuaku, Benjamin (Frontiers in Public Health, 2025)
IntroductionMost studies on loss to follow-up (LTFU) among people living with HIV are done in urban Antiretroviral Therapy (ART) centers that have electronic medical records system. However, there are limited studies in ART centers in rural areas that rely solely on paper-based medical records (PBMR). This study aimed to determine the incidence, trends, and predictors of LTFU among people living with HIV at a rural health facility in Ghana that rely on PBMR.MethodsA retrospective cohort analysis of 232 HIV registrants who received care at St. Theresa’s Hospital, Nandom Municipality, Ghana between 2018 and 2022 was conducted. The Kaplan–Meier method was used to determine failure probabilities, and the Cox proportional hazard regression was used to identify predictors of LTFU.ResultsThe incidence proportion of LTFU was 24.14%, with a rate of 9.57 per 1,000 p-m. There was a significant decline in cases of LTFU from 2018 to 2022, although registrants under 25 years and males exhibited an increase in LTFU risk from 2021 to 2022. Registrants who had a viral load of 1,000 copies or more had an increased risk of LTFU (aHR = 3.52, 95% CI: 1.39–9.00). Conversely, adherence to ART (aHR = 0.28, 95% CI: 0.12–0.68), HIV status disclosure (aHR = 0.34, 95% CI: 0.14–0.84), and being in WHO stage 2 (aHR = 0.10, 95% CI: 0.03–0.31) or stage 3 (aHR = 0.21, 95% CI: 0.08–0.52) acted as protective factors for LTFU.ConclusionThis study identified key predictors of LTFU among people living with HIV in a rural health facility, providing valuable insights to the existing literature. Targeted strategies should prioritize viral suppression, support ART adherence, and encourage status disclosure to improve retention, particularly in rural settings.